Influencias recíprocas entre la ginecología y obstetricia europea y la indígena en Uruguay - José Enrique Pons (Les Cahiers ALHIM)
Knowledge about the kind of medicine practiced by the illiterate ethnic groups dwelling in the extension of what I now Uruguay, comes from chronicles written by the Spanish conquerors and some naturalists of other nations. Ethnic medical notions attributed the origin of diseases to supernatural powers, and therapeutic resources were mainly herbal. When Spanish conquerors occupied the territory, they adopted many of the indigenous therapeutic resources for lack of other means, but eventually a slow Europeanization started developing, though native criteria remained for a long while. Lastly, during the late nineteenth century, Uruguayan medicine became westernized, though some native customs rooted in indigenous traditions are still observed in rural areas.